Bank soundness : a banker's guide to controlling asset quality - Matz, Leonard M. (Illinois : Bank Administration Institute, 1988)
The questions posed here and the analyses and proposals set forth in this book are not merely of interest to bank officers and managers responsible for setting loan policies, or making, reviewing, and collecting loans. A much wider audience has a vital stake in this subject
Includes bibliographical references and index.
osc 07/05/2018
Loans
Keywords: Asset and Liability Management